2006
DOI: 10.1073/pnas.0509188103
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase kinase 3 is a pivotal pathway regulating p38 activation in inflammatory arthritis

Abstract: p38 mitogen-activated protein kinase (MAPK) regulates cytokines in arthritis and is, in turn, regulated by MAPK kinase (MKK) 3 and MKK6. To modulate p38 function but potentially minimize toxicity, we evaluated the utility of targeting MKK3 by using MKK3 ؊/؊ mice. These studies showed that TNF-␣ increased phosphorylation of p38 in WT cultured synoviocytes but that p38 activation, IL-1␤, and IL-6 expression were markedly lower in MKK3 ؊/؊ synoviocytes. In contrast, IL-1␤ or LPS-stimulated p38 phosphorylation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 36 publications
4
82
0
Order By: Relevance
“…This is consistent with the well-documented activation of MAPK families in human RA (27)(28)(29)(30). Thus, even in the preclinical disease phase, the joints of the HuTNF-Tg mice showed an activation of these 2 MAPK members, suggesting that p38 MAPK and ERK mediate the cellular effects of TNF right from the start of molecular onset of arthritis.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the well-documented activation of MAPK families in human RA (27)(28)(29)(30). Thus, even in the preclinical disease phase, the joints of the HuTNF-Tg mice showed an activation of these 2 MAPK members, suggesting that p38 MAPK and ERK mediate the cellular effects of TNF right from the start of molecular onset of arthritis.…”
Section: Discussionsupporting
confidence: 87%
“…Mice lacking MKK3, one of the upstream kinases, which activate p38 MAPK, are protected from arthritis induced by transfer of serum from K/BxN mice. The phenotype was associated with strong inhibition of p38 phosphorylation and decreased IL-1␤ production in the inflamed joints (31). Similarly, deletion of the downstream kinase MAPKAP2, one of the best characterized substrates of p38MAPK, protected mice against collagen-induced arthritis.…”
Section: Discussionmentioning
confidence: 92%
“…Importantly, genetic deletion of MAPK kinase (MKK)3, an upstream activator of p38 MAPKs, or of MAPK-activated protein (MAPKAP)2, a downstream effector of p38 MAPKs, has shown to confer protection from arthritis (31,32). Thus, it is particularly important to understand the respective role of the various p38 MAPK isoforms on the course of inflammatory arthritis.…”
mentioning
confidence: 99%
“…Of these two kinases, MKK3 appears to be the most attractive target for studies of genetic deletion, because MKK3-p38 signalling has been shown to be nonredundant in some pathological processes [30,31]. Furthermore, mouse studies have shown that Mkk3 deficiency is protective in models of passive arthritis and streptozotocin-induced pancreatic inflammation [32,33]. In the current study, Mkk3-deficient db/db mice were created and used to examine the role of MKK3-p38 signalling in the development of obesity, hyperglycaemia and nephropathy in the db/db model of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%